Analyzing the Historical Traces of Arabic Language Education as a Basis for Developing Innovative Learning Approaches in the Era of Society 5.0 - Elyatul Mu'awanah; Ahmad Ashfia; Fikri Huzaifi (Al-Lisan: Jurnal Bahasa)
Background: Arabic language education has undergone significant development from the classical period to the modern era, where various traditional methods and learning philosophies were applied to strengthen language understanding and Islamic values. However, in the era of globalization, innovative approaches are needed to address the needs of the current generation who tend to be more dynamic and familiar with digital technology.